Festa, spazio, territorio - Alessandra Broccolini (EtnoAntropologia)
Which is the relationship we can see between festive phenomena and contemporary processes of locality making? And how do festive phenomena speak to us today about the territories they belong to and define forms of inhabiting? In order to answer these questions, the essay seeks to explore the festivity-territory-inhabitation relation through the spatial analysis of a specific ethnographic case, the feast of the Madonna del Monte di Marta (Viterbo, Lazio), broadening the gaze from the inhabited space of the town-city, where the feast is often (but not always) produced in its ceremonial moments, to the entire territory that the feast encompasses and helps to define, both in the construction of a ‘sense of place’ and in the experience and practical action of the same.